ANALISIS FAKTOR KUALITAS PELAYANAN TERHADAP KEPUASAN KERJA PERAWAT DI RUMAH SAKIT UMUM WISATA UIT - Nur Qamariyah; Nursyamsiyah Nursyamsiyah (Lembaga Pengembangan Kinerja Dosen, 2022)
The hospital is a health service agency that focuses on the quality of services provided. Satisfaction is one indicator of the quality of care that nurses provide and become the capital to get patient satisfaction, and maintain loyalty in using services. This study aims to analyze nurses 'perceptions of the quality of care for nurse job satisfaction at Polewali Mandar Regional General Hospital. It is used as an analytic observational study with a cross sectional study design. The populationsare 117 nurses in Polewali Mandar Hospital, with 53 samples. Data are analyzed by univariate, bivariate with the chisquareanalysistest, and multivariate with logistic regression analysis test.The results showed that there was an effect of direct evidence on nurses' perceptions about service quality on nurse job satisfaction with a value of p = 0,038 (p<0.05). There were an influence of reliability on nurses' perceptions about service quality on nurse job satisfaction with a value of p = 0.019 (p<0.05). There were an effect of responsiveness to nurses' perceptions of service quality about nurse job satisfaction with a value of p = 0.018 (p<0.05). There were a guarantee effect on nurses' perceptions of service quality on nurse job satisfaction with a value of p = 0.039 (p<0.05). There were an influence of empathy on nurses' perceptions about service quality on nurse job satisfaction with a value of p = 0.036 (p <0.05). The most influential variable on nurse job satisfaction weretangible with a value of p = 0,024 (p<0,025).The conclusions of this study are direct evidence,reliability, responsiveness, assurance, and empathy affect to nurse job satisfaction. It is recommended that hospital management must give attention and improve nurse job satisfaction because it is one indicator of the quality of health services.